Как вы объединяете как термины в \((2a + 3) ^ { 2} + ( a - 5) ^ { 2}\)?

0
0

Как вы объединяете как термины в \((2a + 3) ^ { 2} + ( a — 5) ^ { 2}\)?

0
0

\[5a^2+2a+34\] Объяснение:

Используя формулы \[(a+b)^2=a^2+2ab+b^2\] \[(a-b)^2=a^2-2ab+b^2\] мы получили \[4a^2+9+12a+a^2-10a+25\] а это \[5a^2+2a+39\]

0
0

\[5a^2+2a+34\] Объяснение:

Сначала ПОЛЬЗУЙТЕ квадратные условия: \[=(2a+3)^2+(a-5)^2\] \[=(2a+3)(2a+3)+(a-5)(a-5)\] \[=4a^2+6a+6a+9+a^2-5a-5a+25\] Теперь «объединить как термины»: \[=5a^2+2a+34\]

Показано 2 результатов